Letter - Barking Labour Party and Trades Council, 10 May 1926 (?) (Barking)
1926-05-10 "Letter - Barking Labour Party and Trades Council, 10 May 1926 (?)" [g0175001.jpg], 10 May 1926, Barking Labour Party, Trades Council Local Organisation